Study of Electrolyte Levels in Diabetic Patients (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2019)
Diabetes mellitus is a metabolic disorder / disease characterized by high blood glucose levels (hyperglycemia) with changes in carbohydrate, lipid, and protein metabolism in the body due to disruption in insulin action, insulin secretion or both. These metabolic changes affect the concentration of electrolytes. Electrolytes contained in the body play an important role in many body processes, such as controlling fluid levels, acid base balance (pH), nerve conduction, blood clotting and muscle contraction. Sodium, potassium and chloride are the most common macroelectrolytes and correlate with diabetes mellitus. In this study, we examined the prevalence of diabetes and its relationship to electrolyte concentrations in 28 subjects, divided into two groups: group A consisted of 14 diabetic patients in Labuang Baji Hospital and group B consisting of 14 non-diabetic subjects. The results of the research conducted showed that serum electrolyte levels (Na +, K +, Cl-) for the control were all in the normal range. In contrast, serum electrolyte (Na +, Cl-) levels have two patients who have Na + electrolyte levels below the normal range.
Keywords: Diabetes Mellitus; Electrolytes; Sodium; Potassium; Chloride